The Relationship of Loneliness and Internet Addiction To Psychological Well-Being in Adolescents - Hesni Nurmaria; Erna Risnawati (Universitas Mercu Buana Jakarta, 2021)
This study aims to see the relationship between loneliness and internet addiction with the psychological well-being of adolescents in the Greater Jakarta area who actively use the internet. The sampling technique used accidental sampling technique and the sample in the study consisted of 232 adolescents aged 13-21 years. The measuring instrument used is the UCLA Scale Version 3 (University of California Los Angeles Loneliness Scale Version 3) compiled by Rusell (1996), the IAT Scale (Internet Addiction Test) compiled by Young (1998) and the PWB Scale (Psychological Well Being Scale) compiled by Ryff (1995). The results of this study showed that there was no significant relationship between loneliness and psychological well-being and there was no relationship between internet addiction and psychological well-being. However, there is a relationship between loneliness and internet addiction among adolescents.